Implementasi Program Teman Bus Dalam Pengembangan Transportasi Publik Di Kota Denpasar - Ni Luh Putu Ening Permini; I Kadek Deddy Junaedi (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
One of the public services engaged in services provided by the government is transportation services. Transportation is one of the various basic human needs and this is an inseparable part of social life, especially for urban communities, because in daily activities when traveling, access is required to reach every place within a specified effective time. The aim of this research is to find out and analyze the obstacles in implementing the economical, easy, reliable and comfortable transportation policy (Bus Friends) in Denpasar City. The presence of TEMAN BUS in Bali is the third service in the Buy The Service (BTS) program by the Ministry of Transportation of the Republic of Indonesia. The operator that runs the TEMAN BUS service operations is PT. Trans Metro Dewata. The implementation of the Trans Sarbagita Program for 5 (five) years has been able to develop the existence of public transportation, but is still unable to deal with the problem of congestion that occurs on several roads. Implementation of SPM (Minimum Service Standards) is the minimum service standard for Trans Sarbagita Mass Public Transport. The factor that is classified as an obstacle is that Sarbagita does not have a special route, this results in it being unable to reach small areas/areas. Another inhibiting factor is the existence of buses that are starting to break down, so the service provided is less than optimal.